On wings of ash and dust eaudiobook - Wang, Brittany (On Wings of Ash and Dust, 2023)
A rebel pixie princess. A deadly competition between five faerie clans. Will she win the crown or die trying? Pixie pirate Quinn may be an outlaw, wanted by all five faerie clans, but she prefers it that way. All she wants is to finally become a captain and bury her true identity beneath the rolling waves. But when the sudden death of her twin brother causes her to plot a vengeful heist, a shocking betrayal unmasks her for who she really is—her people's last living heir. Her only hope of escaping certain death for her crimes is taking her brother's place in the Ethodine: a dangerous competition for the faerie crown. In a series of death-defying trials, Quinn faces off with the heirs of four rival clans: A mute beast tamer. A flirtatious merman. A half-blind artist. And a pompous princess. But as dark secrets unravel and an ancient prophecy entwines their fates, rivals must become allies before there's no world left to rule. On Wings of Ash and Dust is the action-packed first book in this YA epic fantasy. If you're looking for a fresh take on fae magic, deadly trials, and royal intrigue with a dash of enemies-to-lovers, then you'll adore Brittany Wang's whimsical and dangerous tale. Buy On Wings of Ash and Dust to dive into the adventure today!